II. Electioneering, - Labour Party (Ireland) (1932)
This sub-fonds consists of all the records of the Labour Party concerning electioneering. This includes manifestos, selection convention documentation, referendum campaigns along with local, European and general election files. It also contains records relating to legislative compliance, corporate identity, election planning, market reseach and photographs.